1997
DOI: 10.1243/0954407971526191
|View full text |Cite
|
Sign up to set email alerts
|

Computer aided assessment and optimization of catalyst fast light-off techniques

Abstract: Strict future legislation standards are forcing the car industry to employ new techniques for reducing exhaust gas emissions. Most of these techniques focus on accelerating the appearance of catalyst light-off and are thus called fast light-off techniques (FLTs). Optimized exhaust systems comprising FLTs will be able to meet the forthcoming legislation standards for the United States [low emissions vehicle (LEV) and ultra-low emissions vehicle (ULEV)] and the European Union (Stage III). The most promising acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 17 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…The output of the model is the respective second-bysecond variation in exhaust gas composition and temperature at the catalyst exit, as well as the catalyst bed temperatures [9]. In its present state, the model does not account for particulate matter oxidation in the catalyst.…”
Section: Application Of the Catalytic Converter Modelmentioning
confidence: 99%
“…The output of the model is the respective second-bysecond variation in exhaust gas composition and temperature at the catalyst exit, as well as the catalyst bed temperatures [9]. In its present state, the model does not account for particulate matter oxidation in the catalyst.…”
Section: Application Of the Catalytic Converter Modelmentioning
confidence: 99%
“…Methods to reduce the light-off time in catalysts are generally classified into active or passive systems. Typical active systems include electrically heated catalysts [16], fuel burners [17], secondary air injection [18], and after-burners [19], all of which require an extra energy supply. In contrast, passive systems rely mainly on thermal management of the energy obtained from exhaust gases (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…For any given journey, the first 150 s after the engine start will account for a large proportion of the total emissions produced. A study by Konstantinidis et al 1 found that, for a vehicle equipped with a 2.0 l spark ignition engine and a three-way catalytic converter, the initial 150 s of the urban portion 800 s long of the New European Drive Cycle produced approximately 71% of the CO emissions and 55% of the HC emissions. This is due to the time taken for the catalyst to attain 'light-off', which is signified by the point at which the catalyst reaches a sufficiently high temperature to allow chemical reactions to occur.…”
Section: Introductionmentioning
confidence: 99%